BCG como plataforma vacinal: da imunidade treinada à análise in sílico de peptídeos do SARS-CoV-2 - Campelo, Thales Alves (2025)
First identified in 2019, the SARS-CoV-2 is a Betacoronavirus that triggered a global pandemic, resulting in millions of cases and deaths. Characterized by high transmissibility and the ability to evade the acquired immunity, it infects human cells through the interaction between the Spike protein and the ACE2 receptor, initiating complex immune responses. Given the need for alternative vaccines, the Bacillus Calmette-Guérin (BCG) vaccine, widely used against tuberculosis, stands out for its potential to induce innate/trained and adaptive immunities, as well as its application in heterologous protection against viral infections. In this context, this study conducted an in silico analysis to identify and evaluate SARS-CoV-2- immunogenic peptides, with potential for incorporation into a future recombinant BCG (rBCG) to induce a specific and robust immune response against covid-19. Additionally, the immune mechanisms associated with the trained immunity conferred by BCG were revisited, highlighting its ability to reprogram monocytic cells and induce amplified responses to subsequent infections. The results highlighted the identification of immunogenic peptides derived from SARS-CoV-2, with broad population coverage and the ability to stimulate specific immune responses. Furthermore, it was demonstrated that BCG can reprogram innate immune cells through trained immunity, offering cross-protection against viral infections. The rBCG platform was identified as a viable strategy for the development of multivalent vaccines, combining innate/trained and adaptive immunities to induce effective immune responses. Despite challenges such as genetic stability and variability between strains, the findings reinforce the potential of rBCG in combating emerging diseases and pandemics.